2022
DOI: 10.1101/2022.09.10.507000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-resolution volumetric imaging constrains compartmental models to explore synaptic integration and temporal processing by cochlear nucleus globular bushy cells

Abstract: Bushy neurons of the cochlear nucleus encode temporal fine structure and modulation of sound with high fidelity. However, the synaptic maps and electrotonic structures that underlie these properties are not specified in meaningful explanatory detail. We employed modern volume electron microscopy techniques to provide exact data on the numbers of synaptic inputs and their weights determined by the number of contained active zones, and the surface areas of all postsynaptic cellular compartments. Leveraging these… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 158 publications
(239 reference statements)
0
5
0
Order By: Relevance
“…Bushy neurons are known for their unique bush-like cellular morphology (Brawer et al, 1974; Cant and Morest, 1979; Tolbert et al, 1982; Rouiller and Ryugo, 1984). Despite decades of research, studies that characterize both bushy cell morphology and the comprehensive innervation pattern of connecting AN synapses are rare (Spirou et al, 2022), especially regarding to AN synapses on dendrites, the subtype-specificity of AN synapses, and changes of these features during ARHL. Combining electrophysiology and immunohistochemistry, we developed the technique to investigate both the physiology and morphology of individual bushy neurons and their AN synapses in young and aged mice (Wang et al, 2021; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bushy neurons are known for their unique bush-like cellular morphology (Brawer et al, 1974; Cant and Morest, 1979; Tolbert et al, 1982; Rouiller and Ryugo, 1984). Despite decades of research, studies that characterize both bushy cell morphology and the comprehensive innervation pattern of connecting AN synapses are rare (Spirou et al, 2022), especially regarding to AN synapses on dendrites, the subtype-specificity of AN synapses, and changes of these features during ARHL. Combining electrophysiology and immunohistochemistry, we developed the technique to investigate both the physiology and morphology of individual bushy neurons and their AN synapses in young and aged mice (Wang et al, 2021; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Dendrites are generally viewed as the main site of a neuron to receive incoming synaptic inputs, which is unlikely the case in bushy neurons. Gomez-Nieto and Rubio (2009, 2011) and Spirou et al (2022) reported that bushy neurons receive small AN synapses on the dendrites, which presumably help transmit sound information from the cochlea. Our measurement showed that the total volume of dendritic synapses is only 26% of the somatic synapses on average in bushy neurons from normal hearing young mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations